Implementasi Kebijakan Penurunan Stunting di Kecamatan Pangkalan Kerinci oleh Dinas Pemberdayaan Perempuan Perlindungan Anak Pengendalian Penduduk dan Keluarga Berencana Kabupaten Pelalawan - Pitaloka, Sella (JURNAL RISET INOVASI DAERAH, 2024)
Stunting is a major nutritional problem that will have an impact on social and economic life in society. Stunting can also occur since the fetus in the womb due to problems with lack of protein intake when the mother is pregnant and can also be influenced by environmental conditions. The purpose of this study was to determine and analyze the Implementation of Stunting Reduction Policies in Pangkalan Kerinci District by the Pelalawan Regency Women's Empowerment, Child Protection, Population Control and Family Planning Office based on indicators of Communication, Resources, Disposition, and Bureaucratic Structure.The research type is descriptive qualitative. The number of research informants was 5 people with the Head of DPPPAPPKB as the key informant. Data collection techniques with interviews and data analysis in this study using data analysis techniques in the site developed by Miles Huberman. Based on the results of research and discussion, it can be concluded that the Implementation of Stunting Reduction Policies in Pangkalan Kerinci District by the Pelalawan Regency Women's Empowerment, Child Protection, Population Control and Family Planning Office has not been optimally implemented and needs to be improved. This is because in quality, the human resources of health workers in the field are in accordance with the competencies needed in handling stunting. However, posyandu cadres should be given regular training, especially regarding children at risk of stunting.